Blended learning in higher education: a review of the literature - Bolandifar, Saeideh; Noordin, Nooreen (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The rapid development of technological innovations in higher education has led institutions to turn from traditional face to face classes to blended courses. This article reviews the theoretical and empirical existing studies on blended learning in higher education. First, the definition of blended learning is discussed. Then, the advantages of using blended courses in learning process, the students’ perception of blended learning, and some recommendations for instructional designers are highlighted.